The Effects of Thermoform Molding Conditions on Polyvinylchloride and Polyethylene Double Layer Package Materials - (:unkn) unknown (JOHN WILEY & SONS INC, 2009)
This work reports the effects of thermoform molding process conditions on polyvinylchloride (PVC) and polyethylene (PE) double layer package materials. Mechanical and microstructural properties of the package material were examined by different test methods which are tensile properties, tear resistances and scanning electron microscopy (SEM). Furthermore, package materials, which are produced in different conditions by thermoform molding. Effect of different mold depths and process temperatures on the samples are determined by thermal aging process at 60 degrees C in first, third, and seventh days. With increase in mold depth from 25 mm to 75 mm, there is a significant increase in tensile strength from similar to 45 MPa to similar to 55 MPa, thermoform temperature at 150 degrees C. The highest elongation of the material was obtained thermoform temperature at 165 degrees C as 80%, mold depth at 35 mm. Tensile strength and elongation (%) of the material generally decrease by aging time with changing of mold depth (25, 35, and 75 mm) of the double layer package material. In addition, tear resistances of the material decrease via aging time in various thermoform temperatures (150 degrees C, 165 degrees C, and 175 degrees C) due to the orientation of the segments. Scanning electron microscopic (SEM) images of the materials were taken for aging process in first, third, and seventh days. POLYM. ENG. SCI., 49:2234-2241, 2009. (C) 2009 Society of Plastics Engineers
Keywords: CARBON-FIBER MICROELECTRODES; ELECTROCHEMICAL IMPEDANCE SPECTROSCOPY; FABRIC DEFORMATION; BEHAVIOR; SHEAR